The number of erupted teeth as a risk factor for dental caries in eighteen-month-old children: a cross‑sectional study - Masatoshi Otsugu; Yusuke Mikasa; Maika Kadono; Taro Matsuoka; Katsura Matsunami; Motomi Nakamura; Yuko Ohno; Takafumi Kato; Kazuhiko Nakano (BMC, 2023)
Abstract Background Dental caries is one of the most common chronic diseases worldwide, affecting lifelong as well as children. Therefore, it is important to clarify factors related to early childhood caries (ECC) in a younger population in terms of caries prevention. However, the prevalence of ECC is low in developed countries in the twenty-first century and a large-scale survey is needed to clarify the risk factors. Furthermore, earlier tooth eruption is not taken into consideration in most studies of ECC, even though it may be a factor of ECC. The present study investigated the prevalence and risk factors of dental caries in children aged 18 months in a core city of Japan. Methods Findings from a total of 7351 children aged 18 months were analyzed. Anthropometric measurements of height and weight, as well as an oral examination and a microbiological caries-risk test, were performed. Additionally, a structured interview sheet was provided to the parents or guardians. Findings of dental caries at 18 months of age were evaluated using a logistic regression model. Results Of the enrolled children, 1.2% had experienced dental caries. Multivariable logistic regression analysis results indicated a significant association with dental caries at 18 months of age for the following factors: second child (OR = 1.78; 95% CI:1.08-2.93, P < 0.05), third and later child (OR = 2.08; 95% CI:1.12-3.89, P < 0.05), 12 or fewer erupted teeth (OR = 0.47; 95% CI:0.24-0.96, P < 0.05), 17 or more erupted teeth (OR = 4.37; 95% CI:1.63-11.7, P < 0.01), Cariostat score (+ + +) (OR = 3.99; 95% CI:1.29-12.31, P < 0.05), daily eating before bed (OR = 2.62; 95% CI: 1.55-4.45, P < 0.001), three or more snacks per day (OR = 2.03; 95% CI:1.15-3.58, P < 0.05), and breastfeeding (OR = 3.30; 95% CI:2.00-5.44, P < 0.001). Conclusions These results suggest that the number of erupted teeth, as well as birth order, eating habits, and breastfeeding, are significant factors in dental caries occurrence at 18 months of age.